Designing an English for Specific Course for Teachers Training College Students - Munthe, Melda Veby Ristella (Journal of English Teaching as a Foreign Language, 2018)
This paper attempted by measuring and designing the course of English for Specific Purposes especially for the teachers training college students. English for Specific Purposes surveys the development and classification of ESP areas, The basic principles and techniques in ESP design were covering the Syllabus, Materials and Methodology of assessment. ESP depends to the learners needs. ESP can be classified into the two parts, Such as: EAP (English for Academic Purpose) and EOP (English for Occupational Purpose). In this study,Tthis research is focused on the ESP which is referring to the EAP. The study of ESP for this case is based on the learners‟ needs. The researcher was given some questionnaires to the learners that will be the next students in ESP class. Then, the researcher was taken the data by collecting the data. Afterwards, the researcher was analyzed the data by taking the percentage of the research. Last, the researcher was designed the course design, syllabus and lesson plan of teaching.